OPTIMASI TURBIN ARUS LAUT TIPE V-SHAPED BLADE DENGAN MEMPERTIMBANGKAN BLADE ASPECT RATIO DAN SOLIDITY - Rizki Mendung Ariefianto; Rini Nur Hasanah; Wijono Wijono (Jurnal Teknologi, 2023)
The V-shaped blade turbine is one of the turbine models with good self-starting capability, although its efficiency is still standard. Various studies, especially of foil shape and blade swept angle variations applied to V-shaped blade turbines, have been carried out to improve its performance. This study aims to optimize the ability of a V-shaped blade turbine in terms of efficiency and self-starting by investigating the effect of blade aspect ratio and solidity through several test scenarios. NACA 634021 foil and a blade swept angle of 30Â° were used to create the main form of a V-shaped blade turbine. The simulation results using the QBlade software show that the blade aspect ratio and solidity significantly affect the efficiency and self-starting capability of the V-shaped blade turbine. Finally, the optimal design configuration was achieved on the turbine dimensions with a height of 3.1344 m, a radius of 1.8288 m, a chord foil length of 0.2134 m, and a total of four blades. This configuration can achieve maximum efficiency of 0.441 and fulfills self-starting at the minimum tip speed ratio limit of 0.7.